ELT MATERIALS FOR BASIC EDUCATION IN BRAZIL: IS THERE ROOM FOR AN ELF-AWARE PRACTICE? - Siqueira, Sávio (Estudos Linguísticos e Literários, 2020)
It is a fact that ELT practices around the world have historically been ENL-oriented and inner-circle emulating. It is also a fact that such status quo has been overtly challenged in many contexts. Despite signs of resistance and the chronic lack of dialogue between Academia and school realities, it is plausible to say that ELF and its research findings are slowly gaining ground in regular ELT classrooms, especially due to the inclusion of ELF-related issues in teacher education programs, both at pre-service and in-service levels. This article is based on a brief study conducted in a pre-service teacher education program at Bahia Federal University (UFBA), Salvador, Brazil, whose objective was to analyze how a few English textbooks approved by the National Textbook Program (Programa Nacional do Livro Didático) for local public high schools are linguistically, methodologically, and ideologically conceived, and to what extent their activities were adaptable to an alternative ELF-aware orientation. It then aims to share and discuss some of the results of the referred study, including examples of activities, assuming that an ELF-aware pedagogy in EFL-oriented contexts is perfectly viable, even when departing from pre-existing materials which already take into consideration features of the local reality and how English can be realistically used by these specific speakers.